Development of a nanobody-based lateral flow immunoassay for detection of human norovirus - Doerflinger, Sylvie; Tabatabai, Julia; Schnitzler, Paul; Koromyslova, Anna D.; Hansman, Grant S. (mSphere, 2016)
We previously identified a Nanobody (termed Nano-85) that bound to a highly conserved region on the norovirus capsid. In this study, the Nanobody was biotinylated and gold conjugated for a lateral flow immunoassay (termed Nano-IC). We showed that the Nano-IC assay was capable of detecting at least four antigenically distinct GII genotypes, including the newly emerging GII.17. In the clinical setting, the Nano-IC assay had sensitivities equivalent to other commercially available lateral flow systems. The Nano-IC method was capable of producing results in ~5 min, which makes this method useful in settings that require rapid diagnosis, such as cruise ship outbreaks and elder care facilities. The Nano-IC assay has several advantages over antibody-based IC methods: for example, Nanobodies can be readily produced in large quantities, they are generally more stable than conventional antibodies, and the Nanobody binding sites can be easily obtained by X-ray crystallography., Human noroviruses are the dominant cause of outbreaks of acute gastroenteritis. These viruses are usually detected by molecular methods, including reverse transcriptase PCR (RT-PCR) and enzyme-linked immunosorbent assay (ELISA). Human noroviruses are genetically and antigenically diverse, with two main genogroups that are further subdivided into over 40 different genotypes. During the past decade, genogroup 2 genotype 4 (GII.4) has dominated in most countries, but recently, viruses belonging to GII.17 have increased in prevalence in a number of countries. A number of commercially available ELISAs and lateral flow immunoassays were found to have lower sensitivities to the GII.17 viruses, indicating that the antibodies used in these methods may not have a high level of cross-reactivity. In this study, we developed a rapid Nanobody-based lateral flow immunoassay (Nano-immunochromatography [Nano-IC]) for the detection of human norovirus in clinical specimens. The Nano-IC assay detected virions from two GII.4 norovirus clusters, which included the current dominant strain and a novel variant strain. The Nano-IC method had a sensitivity of 80% and specificity of 86% for outbreak specimens. Norovirus virus-like particles (VLPs) representing four genotypes (GII.4, GII.10, GII.12, and GII.17) could be detected by this method, demonstrating the potential in clinical screening. However, further modifications to the Nano-IC method are needed in order to improve this sensitivity, which may be achieved by the addition of other broadly reactive Nanobodies to the system., IMPORTANCE We previously identified a Nanobody (termed Nano-85) that bound to a highly conserved region on the norovirus capsid. In this study, the Nanobody was biotinylated and gold conjugated for a lateral flow immunoassay (termed Nano-IC). We showed that the Nano-IC assay was capable of detecting at least four antigenically distinct GII genotypes, including the newly emerging GII.17. In the clinical setting, the Nano-IC assay had sensitivities equivalent to other commercially available lateral flow systems. The Nano-IC method was capable of producing results in ~5 min, which makes this method useful in settings that require rapid diagnosis, such as cruise ship outbreaks and elder care facilities. The Nano-IC assay has several advantages over antibody-based IC methods: for example, Nanobodies can be readily produced in large quantities, they are generally more stable than conventional antibodies, and the Nanobody binding sites can be easily obtained by X-ray crystallography.